Rectal neuroendocrine tumor: a case series - Kamarudin, Zalikha; Ganisan, Dhayalan; Mahno, Noor Ezmas (2017)
The gastrointestinal (GI) tract contains no fewer than 13 different types of neuroendocrine cells.( 1)Although the GI tract have the largest amount of neuroendocrine cell, the occurrence of GI NETs are rare and only constitute less than 2 % of all GI malignancies. Rectal NETs are the second most common GI NETs after small bowel. Most of the cases discovered incidentally during screening colonoscopy for other reasons. (2)